Surveillance of Disease Progression in Metastatic Breast Cancer by Molecular Counting of Circulating Tumor DNA Using Plasma-SeqSensei Breast Cancer in Vitro Diagnostics Assay - Martens, Geert A.; Demol, Jan; Dedeurwaerdere, Franceska; De Smet, Kristof; Wesolowski, Janusz; De Smet, Dieter (The Journal of molecular diagnostics : JMD, 2025)
Circulating tumor DNA (ctDNA) quantification surpasses cancer antigen 15 to 3 for metastatic breast cancer surveillance. Clinical translation, however, is limited because of uncertainties about the optimal method and clinically valid ctDNA decision thresholds. Plasma-SeqSensei Breast Cancer IVD kit (PSS) is a novel assay for ctDNA molecular counting, detecting ≥0.06% variant allele fractions in AKT1, ERBB2, ESR1, KRAS, PIK3CA, and TP53. PSS was validated against droplet digital PCR (ddPCR) in 201 samples from 16 subjects with PIK3CA/TP53-mutated cancers, longitudinally sampled for a median of 93 (range, 18 to 113) weeks, three to five weekly. PSS and ddPCR ctDNA levels correlate significantly (Spearman ρ, 0.923; 95% CI, 0.898–0.941) across 0% to 43% variant allele frequency (VAF) range. PSS predicts 12-week progression with high clinical accuracy (area under the curve, 0.848; 95% CI, 0.790–0.894). PSS validates a previously developed ddPCR classifier: <10 copies/mL (0.25% VAF); excludes >100 copies/mL (2.5% VAF); and confirms progression, with negative predictive value (95% CI) of 83% (76%–88%) and positive predictive value (95% CI) of 91% (81%–96%) (weighted κ, 0.856; 95% CI, 0.797–0.915). PSS thus confirms robust clinical thresholds (10 to 100 copies/mL, 0.25% to 2.5% VAF) for metastatic breast cancer surveillance, using absolute molecular counting.